Misdiagnosis of Streptococcus gallolyticus endocarditis - Starosta, Rodrigo Tzovenos; Rivero, Raquel; Oliveira, Francine Hehn de; Lopes, Eron; Cerski, Marcelle Reesink (Autopsy and Case Reports, 2016)
Death certificate inaccuracy is of major concern both in the public health domain and in individual health care, since it may yield untruthful data on the incidence, prevalence, and lethality of medical entities, and may hamper prophylactic measures among those who share, with the deceased, the common genetic, environmental, or behavioral risk factors. An effective way to settle this haziness relies on the increase of autopsy performance, increasing manifold the exactitude as well as facing surprising diagnoses. In this report, the authors present the case of a middle-aged woman who sought medical care because of back pain accompanied by weight loss. She died suddenly and unexpectedly in the Emergency Room. In this case, due to the unusual clinical presentation and the patient’s unexpected death, the causa mortis would not have been elucidated if the autopsy had not been undertaken